Pengaruh Penggunaan Alat Peraga Terhadap Hasil Belajar IPA Siswa Kelas V SDN Bojongkacor Bandung Pada Materi Perpindahan Kalor - Tarigan, Linda Fahira Br.; Yudiyanto, Mohamad; Nurishlah, Laesti; Mulyani, Ani Sri (MURABBI, 2024)
This study examines student activity, responses to visual aids, and science learning outcomes concerning heat transfer in fifth-grade students at SD Negeri Bojongkacor, Bandung Regency, utilizing a thermoscope as a visual aid. This topic is significant as active engagement and positive responses to visual aids can enhance conceptual understanding and learning outcomes. The research employs a quantitative methodology involving experimental and control groups, with data collected through student activity observation, response questionnaires, and learning tests (pretest and posttest). Observations revealed that 76.90% of students actively engaged with the visual aid, surpassing the minimum criterion of 75%. Students' responses to the thermoscope were highly positive, with a percentage of 91%. The experimental group exhibited a posttest average score of 78.17, significantly higher than the control group's average of 68.19. Hypothesis testing using a t-test indicated a significance level of 0.038, suggesting that the use of the thermoscope significantly enhances student learning outcomes compared to conventional methods. This study underscores the critical role of visual aids in improving science education effectiveness.